Epidemiology of injuries in National Collegiate Athletic Association men's lacrosse: 2014-2015 through 2018-2019 - D'Alonzo, B. A.; Bretzin, A. C.; Chandran, A.; Boltz, A. J.; Robison, H. J.; Collins, C. L.; Morris, S. N. (Journal of Athletic Training, 2021)
Context: The popularity of National Collegiate Athletic Association (NCAA) men's lacrosse has been steadily increasing since the early 1980s. Background: Injury surveillance is an important tool to aid in identifying emerging patterns of sport-related injury in NCAA men's lacrosse. Methods: Injury data collected from a sample of men's lacrosse teams through the NCAA Injury Surveillance Program for the academic years 2014-2015 through 2018-2019 were analyzed. Athlete exposures were estimated and computed based on collected exposure data. Injury counts, rates, and proportions were used to describe injury characteristics, and injury rate ratios (IRRs) with 95% confidence intervals (CIs) were calculated to estimate differences in injury rates. Results: The overall injury rate was 4.90 per 1000 athlete exposures (AEs), and the competition injury rate was higher than the practice injury rate (IRR = 2.59; 95% CI = 2.35, 2.84). The overall preseason injury rate was higher than the regular and postseason injury rates. The most reported injuries were concussions (8.0%), ankle sprains (7.7%), and hamstring tears (6.9%). Conclusions: Study findings were comparable with existing epidemiological evidence. The overall burden of concussions and lower extremity injuries warrant further attention in this population.